2011
DOI: 10.1155/2011/691348
|View full text |Cite
|
Sign up to set email alerts
|

Infections and Ischemic Stroke Outcome

Abstract: Background. Infections increase the risk of ischemic stroke (IS) and may worsen IS prognosis. Adverse effects of in-hospital infections on stroke outcome were also reported. We aimed to study the prevalence of pre- and poststroke infections and their impact on IS outcome. Methods. We analysed clinical data of 2066 IS patients to assess the effect of pre-stroke and post-stroke infections on IS severity, as well as short-term (up to 30 days) and long-term (90 days) outcome. The independent impact of infections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
21
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 33 publications
(35 reference statements)
5
21
1
Order By: Relevance
“…Two recent studies found no independent influence between PI and 3-month outcome. 9,10 However, the latter study showed unfavorable 30-day outcome in those with PI. 10 Another stroke-related infectious phenomena are poststroke infections (PSIs) that occur during the acute phase (0-7 days after the stroke).…”
mentioning
confidence: 80%
See 4 more Smart Citations
“…Two recent studies found no independent influence between PI and 3-month outcome. 9,10 However, the latter study showed unfavorable 30-day outcome in those with PI. 10 Another stroke-related infectious phenomena are poststroke infections (PSIs) that occur during the acute phase (0-7 days after the stroke).…”
mentioning
confidence: 80%
“…9,10 However, the latter study showed unfavorable 30-day outcome in those with PI. 10 Another stroke-related infectious phenomena are poststroke infections (PSIs) that occur during the acute phase (0-7 days after the stroke). PSIs have frequent medical complications: urinary tract infections occur in 10% to 29% and chest infections in 11.2% to 18% of the cases.…”
mentioning
confidence: 80%
See 3 more Smart Citations